2019
DOI: 10.1029/2018ja025745
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of the POES/MEPED Loss Cone Electron Fluxes With the CMIP6 Parametrization

Abstract: Quantitative measurements of medium energy electron (MEE) precipitation (>40 keV) are a key to understand the total effect of particle precipitation on the atmosphere. The Medium Energy Proton and Electron Detector (MEPED) instrument on board the NOAA/Polar Orbiting Environmental Satellites (POES) has two sets of electron telescopes pointing ~0° and ~90° to the local vertical. Pitch angle anisotropy, which varies with particle energy, location, and geomagnetic activity, makes the 0° detector measurements a low… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…The analysis presented here provides a detailed comparison between satellite >30-keV electron precipitation flux measurements, VLF phase-inferred fluxes, and the CMIP6 predictive flux model during one large geomagnetic storm. The finding that the CMIP6 model of predicted electron precipitation (ApEEP) underrepresents geomagnetic storm-time fluxes is consistent with previous analysis undertaken by Nesse Tyssøy et al (2019), although the underestimate is found to be small. Realistic electron precipitation fluxes, as inferred from VLF signal analysis and POES observations during the storm, could be as large as a factor of 1.7 higher than currently estimated by the ApEEP predictive model (Matthes et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The analysis presented here provides a detailed comparison between satellite >30-keV electron precipitation flux measurements, VLF phase-inferred fluxes, and the CMIP6 predictive flux model during one large geomagnetic storm. The finding that the CMIP6 model of predicted electron precipitation (ApEEP) underrepresents geomagnetic storm-time fluxes is consistent with previous analysis undertaken by Nesse Tyssøy et al (2019), although the underestimate is found to be small. Realistic electron precipitation fluxes, as inferred from VLF signal analysis and POES observations during the storm, could be as large as a factor of 1.7 higher than currently estimated by the ApEEP predictive model (Matthes et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the MLT version of the ApEEP model is required in order to compare against the specific VLF propagation path analyzed. However, van de Kamp et al (2018) showed that the ApEEP_MLT model-predicted fluxes, when zonally averaged, generated fluxes equivalent to that of the non-MLT model used in CMIP6, so we can assume the conclusions of Nesse Tyssøy et al (2019) to also be valid for the ApEEP_MLT modelpredicted fluxes. Figure 9 shows 24-hr average >30-keV electron precipitation fluxes determined using the ApEEP_MLT model, VLF phase perturbations, and the longitudinally restricted POES >30-keV measurements.…”
Section: Validationmentioning
confidence: 95%
See 2 more Smart Citations
“…Both telescopes have a 30 • angle of view and records electron flux in three energy channels: > 30 keV, > 100 keV, and > 300 keV. Unfortunately, the use of POES for electron precipitation measurements have several significant problems, such 150 as proton contamination and varying detector efficiency that are both well-documented in the literature (e.g., Asikainen and Mursula, 2013;Rodger et al, 2010b;Tyssoy et al, 2019). The POES data used here has been corrected for these instrumental problems (Asikainen and Mursula, 2011;Asikainen et al, 2012;Asikainen and Mursula, 2013).…”
mentioning
confidence: 99%